Is Secessionism Mostly About Income or Identity? A Global Analysis of 3,003 Subnational Regions - Klaus Desmet; Ignacio Ortu\~no Ortín; Ömer Özak (Global Labor Organization (GLO), 2022)
This paper analyzes whether the propensity to secede by subnational regions responds mostly to differences in income per capita or to distinct identities. We explore this question in a quantitative political economy model where people's willingness to finance a public good depends on their income and identity. Using high-resolution economic and linguistic data for the entire globe, we predict the propensity to secede of 3,003 subnational regions in 173 countries. We validate the model-based predictions with data on secessionist movements, state fragility, regional autonomy, and conflict, as well as with an application to the dissolution of the Soviet Union. Counterfactual analysis strongly suggests that identity trumps income in determining a region's propensity to secede. Removing identity differences reduces the average support for secession from 7.5% to 0.6% of the population.
Keywords: H77; P00; D70; D74; F02; F52; Z10; 330; Secessionism; Separatism; Federalism; Conflict; Identity; Political Economy; International Relations